KEABSAHAN PEMILIHAN KEPALA DESA DALAM SISTEM OTONOMI DAERAH - Anugrah Patah; Ahmad Rifai Rahawarin; Ariyanto Ariyanto; Desy Maryani (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Abstract: This article study is to understand and analyze the validity of village head elections in the regional autonomy system through a juridical descriptive method with a conceptual approach and a statutory approach. That the validity of the village head election is, (a). the validity of the village head candidate; (b). the validity of the organizers; (c). voter validity; (d). the validity of the pilkades stages; and (e). valid vote. And according to the decision of the State Administration, namely the validity of village head elections must be in accordance with statutory regulations and general principles of good governance, so that the validity of village head elections will become legal in accordance with the principle of legality. If there is a claim from one of the partiesKeywords: Legislation; Election; Village Head; Regional Autonomy.